2010
DOI: 10.1007/978-1-60761-860-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cells: Discovery, Development, and Current Trends

Abstract: Murine embryonic stem cells were first derived almost 30 years ago from cultured blastocysts and have been primarily used as a tool to better understand development through targeted gene deletions. Only recently has the focus has shifted toward embryonic stem cells themselves and the molecular mechanisms by which they choose a specific cell fate. Through rapid advances in cell culture and genomic modification techniques researchers are beginning to regularly utilize embryonic stem cells for in vitro gene funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 159 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The exact mechanisms controlling stemness have not been determined, but the research has revealed key extracellular and intracellular players. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms controlling stemness have not been determined, but the research has revealed key extracellular and intracellular players. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%